Etnokapitalisasi Pariwisata: Analisis Model Pengembangan Cultural Tourism Sunda dalam Mengoptimalkan Multiplier Effect Ekonomi Lokal di Tahura Ir. H. Djuanda - Naysilla Desti Aulia; Yusuf Firmansyah; Beby Rabiul Al Zahra; Nabhan Fajrul Falah; Aqila Nurlaily; Muhamad Nazril; Gloria Gabriella (Journal of Economic and Business Advancement, 2026)
This study examines the role of ethnocapitalization in Sundanese cultural tourism as a strategy to generate local economic multiplier effects. Using a descriptive-analytical literature review approach, the research analyzes academic articles discussing cultural tourism, multiplier effects, and community-based tourism development in Indonesia, with particular relevance to Sundanese cultural contexts. The analysis focuses on key themes including economic impacts, development strategies, community participation, and the commodification of culture. The findings indicate that Sundanese cultural tourism has strong potential to enhance local economic growth by creating employment opportunities, increasing community income, and strengthening local enterprises. At the same time, challenges such as excessive commercialization, unequal benefit distribution, and economic dependency on tourism remain critical issues. Effective governance, inclusive community involvement, and product diversification are essential to balance economic objectives with cultural preservation.